METODE PENDIDIKAN KARAKTER ISLAM MENURUT AHMAD YASIN ASYMUNI (STUDI KITAB TARBIYATUL WALAD) - Achmad Choirul Amin; Muhammad Sueb (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
This research is motivated by the behavior of children today, ranging from violence, delinquency, moral crisis, and so on, this incident cannot be separated from the role of character education from parents and educators. The formulation of the problem of this thesis is first, How is Ahmad Yasin Asymuni’s educational thinking, Second, How is the method of Islamic character education contained in the Tarbiyatul Walad Book by Ahmad Yasin Asymuni, Third, How is the relevance of Islamic character education methods according to Ahmad Yasin Asymuni in the Tarbiyatul Walad Book with Education in Indonesia today. This type of research is qualitative research. The study used a qualitative paradigm with a descriptive analytical approach, while secondary data were obtained from the literature and interviews from families, and the head of the boarding school. The results of the study conclude that the Ahlusunnah wal Jamaah understanding is the understanding of the aqidah adhered to by Ahmad Yasin Asmuni, in terms of fiqh he is of the As-Syafi’i adherents, while in terms of education he adheres to boarding school-style education, Ahmad Yasin’s method of character education for children; first, the method of dialogue of the Qur’an and the Prophet, second, the method of the story of the Qur’an and the Prophet and third, the method of Ibrah and Wisdom. The relevance of Ahmad Yasin’s Islamic character education and character education in Indonesia today is very relevant. This can be proven by the balance of Ahmad Yasin’s method with the character in Indonesia, which also applies Islamic education.Keywords: Ahmad Yasin Asymuni, Method, Character Education Penelitian ini dilatarbelakangi oleh tingkah laku anak saat ini, mulai dari kekerasan, kenakalan, krisis akhlak dan lain sebagainya, kejadian ini tidak bisa terlepas dari peran pendidikan karakter dari orang tua dan pendidik. Rumusan masalah dari tesis ini adalah pertama, Bagaimana pemikiran pendidikan Ahmad Yasin Asymuni, kedua, Bagaimana metode pendidikan karakter Islam yang terkandung dalam kitab Tarbiyatul Walad karya Ahmad Yasin Asymuni, ketiga, Bagaimana relevansi metode pendidikan karakter Islam menurut Ahmad Yasin Asymuni dalam Kitab Tarbiyatul Walad dengan Pendidikan di Indonesia saat ini. Jenis penelitian ini adalah penelitian kualitatif. Penelitian yang menggunakan paradigma kualitatif dengan pendekatan deskriptif analitis, adapun data sekunder diperoleh dari literatur dan wawancara dari keluarga, dan lurah pondok. Hasil dari penelitian menyimpulkan bahwa Paham Ahlusunnah wal Jamaah adalah paham aqidah yang dianut Ahmad Yasin Asymuni, dalam hal fiqh ia bermadzhab As-Syafi’i, sedangkan dari segi pendidikan ia adalah menganut pendidikan ala pesantren, metode pendidikan karakter anak karya Ahmad Yasin; pertama, Metode dialog Qur’ani dan Nabawi, kedua, Metode kisah Qur’ani dan Nabawi dan ketiga, Metode Ibrah dan Hikmah. Relevansi pendidikan karakter Islam Ahmad Yasin dan Pendidikan karakter di Indonesia Masa kini sangat relevan. Hal tersebut bisa dibuktikan dengan seimbangnya metode Ahmad Yasin dengan karakter di Indonesia, yang juga menerapkan pendidikan ajaran Islam.Kata Kunci: Ahmad Yasin Asymuni, Metode, Pendidikan Karakter